Hydrothermal Synthesis of 1D Zn(II) Coordination Polymer - Li, Bin (Asian Journal of Chemistry, 2013)
One new Zn(II) compound [Zn(L)(1,10-phen)]n [H2L = 4,4-(isopropylidene)-bis(benzoic acid) and 1,10-phen = 1,10-phenanthroline] has been successfully synthesized. This compound shows a one-dimensional chain. The carboxylate groups in present compound adopt a bis-chelating coordination mode.